Incentivizing More Effective Marine Protected Areas with the Global Ocean Refuge System (GLORES) - Hameed, Sarah O.; Cornick, Leslie A.; Devillers, Rodolphe; Morgan, Lance E. (Frontiers in Marine Science, 2017)
Healthy oceans are essential to human survival and prosperity, yet oceans are severely impacted worldwide by anthropogenic threats including overfishing, climate change, industrialization, pollution, and habitat destruction. Marine protected areas (MPAs) have been implemented around the world and are effective conservation tools that can mitigate some of these threats and build resilience when designed and managed well. However, despite a rich scientific literature on MPA effectiveness, science is not the main driver behind the design and implementation of many MPAs, leading to variable MPA effectiveness and bias in global MPA representativity. As a result, the marine conservation community focuses on promoting the creation of more MPAs as well as more effective ones, however no structure to improve or accelerate effective MPA implementation currently exists. To safeguard marine ecosystems on a global scale and better monitor progress towards ecosystem protection, robust science-based criteria are needed for evaluating MPAs and synthesizing the extensive and interdisciplinary science on MPA effectiveness. This paper presents a strategic initiative led by the Marine Conservation Institute called the Global Ocean Refuge System (GLORES). GLORES aims to set standards to improve the quality of MPAs and catalyze strong protection for at least 30% of the ocean by 2030. Such substantial increase in marine protection is needed to maintain the resilience of marine ecosystems and restore their benefits to people. GLORES provides a comprehensive strategy that employs the rich body of MPA science to scale up existing marine conservation efforts.